Analysis of the solar sail deformation based on the point cloud method. Issue 9 (1st May 2021) - Huang, Xiyao; Zeng, Xiangyuan; Circi, Christian; Vulpetti, Giovanni; Qiao, Dong
Abstract: The deformation of the solar-sail membrane is an important factor for causing inaccuracies in the solar-sail missions. This paper describes the solar sail under deformation by using a new modelling technique based on point cloud and triangular mesh generation. Two types of deformation, stemming from wrinkling and billowing, are modelled. The changes in the solar radiation pressure force and the moment caused by deformation are calculated and compared to the ideal non-deformed case. The heliocentric spiral trajectory and the orbital angular momentum reversal trajectory are taken as examples to quantify the influence of the deformation from an orbit point of view. Additionally, point cloud simplification, based on the normal vector and bounding box, is utilized to simplify the original deformed-sail model. It involves a reasonable reduction and renewal of the points in the model considering the variation of surface curvature. The simplification and its modelling accuracy are numerically investigated as well as computational efficiency.